1970
DOI: 10.1007/bf02531471
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of fatty acids by heat treated hemoproteins

Abstract: The hemoproteins catalase and peroxidase, after heat treatment which decreased their enzyme activities, became more efficient as heme catalysts of linoleic acid oxidation. These effects might be of importance for preservation and storage of food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Some of this activity may originate from lipoxygenases because these enzymes have been demonstrated in skin of sardine in at least three studies (18,54,55). The response of dark muscle extracts to heating is probably more complex and reflects several simultaneous reactions, e.g., denaturation of hemoproteins (56,57) and inactivation of microsomal enzymes (9,58). Concerning the former, Fujimoto et al (55) actually found sardine dark muscle to yield a higher pro-oxidative activity after cooking, something which is most likely related to the exposure/liberation of heme groups (57).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this activity may originate from lipoxygenases because these enzymes have been demonstrated in skin of sardine in at least three studies (18,54,55). The response of dark muscle extracts to heating is probably more complex and reflects several simultaneous reactions, e.g., denaturation of hemoproteins (56,57) and inactivation of microsomal enzymes (9,58). Concerning the former, Fujimoto et al (55) actually found sardine dark muscle to yield a higher pro-oxidative activity after cooking, something which is most likely related to the exposure/liberation of heme groups (57).…”
Section: Resultsmentioning
confidence: 99%
“…The response of dark muscle extracts to heating is probably more complex and reflects several simultaneous reactions, e.g., denaturation of hemoproteins (56,57) and inactivation of microsomal enzymes (9,58). Concerning the former, Fujimoto et al (55) actually found sardine dark muscle to yield a higher pro-oxidative activity after cooking, something which is most likely related to the exposure/liberation of heme groups (57). According to Undeland et al (59), different hemoproteins responded in different ways to heating at 55 and 100°C; myoglobin increased its pro-oxidative activity, whereas the inverse was seen for hemoglobin.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of haemoproteins necessary to give the observed rates of fatty acid oxidation would be much higher than the maximum possible in our preparations. For example, Eriksson, Olsson & Svensson (1970) showed that the rate of linoleate oxidation in the presence of undenatured catalase was 20,umol of 02 consumed/min per ,umol of haemoprotein. The partially purified lipoxygenase enzyme from potato contained less than 0.1 nmol of haematin/mg of protein.…”
Section: Resultsmentioning
confidence: 99%
“…The increased susceptibility of EtOH-extracted brown rice kernels to oxidative deterioration could be attributed to ethanolic-and heat-denaturation of the hemoproteins catalase and peroxidase found in the kernel . Eriksson et al (1969) demonstrated that the rate of linoleic acid oxidation in the presence of heat-denatured catalase and peroxidase increased as much as 11 times over that for unheated controls. St.…”
Section: Results and Discussion Extraction Temperature And Time Effectsmentioning
confidence: 99%